(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: In the current era of eco-friendly and environmental strategies, waste practices like recycling offer potential benefits for the hotel industry. However, research supporting the financial advantages of these practices is still lacking. Objective: This study aims to explore the waste management which is being produced by the hotel sector and recycle practices which are adopted by the hotel. The study also evaluates the potential environmental benefits of recycling, particularly in relation to reducing greenhouse gas (GHG) emissions. Methodology: Primary data was collected via a questionnaire distributed to 37 hotels, of which 22 expressed interests in completing the questionnaire and participating in face-to-face interviews. SPSS was used for the data analysis and thematic analysis used for analyzing the interview data. Locale of the study was Delhi NCR, Region. Results: The paper’s findings reveal a total waste volume of 584.33 units, with 212.16 units distributed across the different categories such as plastic bottles, other plastic, aluminum etc. The results suggest that hotels need to implement more stringent recycling practices, which would not only benefit the environment but also unlock potential financial advantages. Additionally, promoting guest involvement in recycling initiatives is advised to improve cost-effectiveness and profitability within the industry. Conclusion: Effective waste management and recycling practices are essential for enhancing sustainability in the hotel industry.